Band‐Gap Manipulations of Monolayer Graphene by Phenyl Radical Adsorptions: A Density Functional Theory Study. Issue 12 (12th June 2014) - Huang, Lin; Sk, Mahasin Alam; Chen, Peng; Lim, Kok Hwa
Abstract Phenyl radical (Ph.) adsorption on monolayer graphene sheets is used to investigate the band‐gap manipulation of graphene through density functional theory. Adsorption of a single Ph. on graphene breaks the aromatic π‐bond and generates an unpaired electron, which is delocalized to the ortho or para position. Adsorption of a second radical at the ortho or para position saturates the radical by electron pairing and results in semiconducting graphene. Adsorption of a second radical at the ortho position (ortho–ortho pairing) is found to be more favorable than adsorption at the para position (ortho–para pairing), and the ortho–ortho pairing has stronger effects on band‐gap opening compared with ortho–para pairing. Adsorption of even numbers of Ph. on graphene by ortho–ortho and ortho–para pairings, in general, increases the band gap. Our study shows promise of band‐gap manipulation in monolayer graphene by Ph. adsorption, leading to potential wider applications of graphene.